Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Constructing a dual-active-phase Li4SiO4/Li3NaSiO4 system through Na2CO3/NaCl codoping for enhanced thermochemical energy storage - Jian Chen; Rui Shen; Yan Qi; Hanlei Yu; Tao Fang; Xue Bu; Ziheng Xu; Han Ye; Youshi Li; Bocheng Yu; Hui Zhou (Chemical Engineering Journal, 2026)

Biodiversity and paleoenvironmental reconstruction of the Jehol Biota in the Jiufengshan Formation of eastern Inner Mongolia, northeastern China - Yan Xue; Zhenhua Jing; Xiao Teng; Xin Zhang; Peihan Liu; Siyu Song; Rui Fang; Gang Li; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Early Cretaceous Jehol Biota in the Qinling Orogenic Belt: palaeobiogeographical and palaeoecological implications - Siyu Song; Xin Zhang; Xiao Teng; Ting Li; Tingting Yu; Jiahao Li; Yan Xue; Peihan Liu; Rui Fang; Xiangdong Zhao; Daran Zheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Rhizosphere microbiome and soil health effects on ginseng growth performance and ginsenoside accumulation - Jing Fang; Rui Liu; Kemeng Zhang; Yingmei Sun; Yan Xue; Changbao Chen; Tao Zhang; Qinghe Zhang; Jia Chen (Plant and Soil, 2026)

Short-term hot spring balneotherapy ameliorates sleep disorders: wrist-worn wearable-assessed sleep improvement associated with neuroimmune, tryptophan metabolic and gut microbiome alterations - Xiao Zhang; Yue Zou; Xiao-qin He; Yi-hang Xu; Hong-xia Li; Fen Yang; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Si-fan Hao; Meng-meng Wang; et al. (International Journal of Biometeorology, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

DICP1-A precisely degrades STING-A but not STING-B to suppress IFN expression through the autophagic pathway in gibel carp - Yue Wu; Shun Li; Fan-Xiang Gao; Zhi Li; Rui-Hai Gan; Can Zhang; Xiao-Li Yang; Zhuo-Cong Li; Chu-Jing Zhou; Yang-Yang Wang; Na Xu; Xue-Bing Wang; et al. (Aquaculture, 2026)

Laminarin attenuates neuroinflammation in MPTP-induced Parkinson’s disease mouse model via inhibiting dectin-1/Syk/NF-κB signaling - Rui-Yue Zhao; Mei Zhang; Xiao-Wen Wang; Feng Xue; Yang-Yang Zheng; Wen-Fang Chen (Inflammopharmacology, 2026)

Binasal occlusion modulates cortical functional connectivity and hemodynamics in acquired paralytic esotropia: a fNIRS study - Jie Zhou; Ran Du; Xue Wang; Jun Wu; Fubiao Huang; Rui Fang; Yixiong Liang; Ning Song; Wenbin Wei (Experimental Brain Research, 2026)

Large-scale REE mineralization linked to intensive evolution of carbonatitic-alkaline magmas to brine-melts: Insights from Sr-Nd-Ba isotopes - Xiao-Chun Li; Geng-Xin Deng; Xiao-Yun Nan; Xue-Yin Yuan; Hong-Rui Fan; Fang Huang (Geochemistry, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Forest greenness stability in response to climate change along forest edge–core gradients - Shaodong Huang; Rui Li; Yujie Li; Siyu Xue; Panfei Fang; Yuying Liang; Jia Wang; Longhuan Wang (Agricultural and Forest Meteorology, 2025)

Groundwater anomaly variation and its response to environment change in an inland river basin, China - Zexia Chen; Wei Liu; Qi Feng; Zhenliang Yin; Meng Zhu; Yuanyuan Xue; Lingge Wang; Chunshuang Fang; Rui Zhu (Journal of Hydrology, 2025)

Cr(VI)-bioremediation mechanism of a novel strain Bacillus sp. Cr02 with simultaneous aerobic/anaerobic reduction for Cr(VI) from soil to groundwater - Liping Liu; Rui Liu; Fang Wang; Yujun Wu; Fei Ge; Jiang Tian; Feng Li; Shengguo Xue (Journal of Hazardous Materials, 2025)

Xylem hydraulic impairment due to stronger drought stress accounts for the reduced crown vitality and growth performance of Mongolian pine trees in higher-density plantations - Xue-Wei Gong; Yi-Lei Ouyang; Yan-Yan Liu; Jin-En Zhang; Zhao-Kui Li; Hong-Li Li; Zhuo-Qun Fang; Yu Cao; De-Dong Wu; Qiu-Rui Ning; Guang-You Hao (Agricultural and Forest Meteorology, 2025)

Insight into unloading and geostress characteristics of high slopes based on valley evolution: a case study in Luding county, China - Hongfu Zhou; Shuwu Li; Fan Yang; Tian Fang; Rui Li; Jingyi Xue; Jinpeng Hu; Jiang Xing (Bulletin of Engineering Geology and the Environment, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Root exudates drive root avoidance of maize in response to neighboring wheat - Xiao-Tong Yin; Fang-Fang Zhang; Rui-Peng Yu; Na Liu; Wei-Ping Zhang; Dario Fornara; Liesje Mommer; Xue-Xian Li; Long Li (Plant and Soil, 2025)

Atmospheric carbonyls in urban Beijing in the summertime under the continuous implementation of clean air actions: Decreasing trends, source apportionments and new insights for control strategies - Xin Zhang; Fang Bi; Mingzhu Li; Lu Zhao; Hao Zhang; Yunfeng Li; Likun Xue; Rui Gao; Yujie Zhang; Xuezhong Wang; Zhenhai Wu; Zhanshan Wang; et al. (Journal of Cleaner Production, 2025)

Purification of solid waste phosphogypsum by various cationic collectors: Experimental study and theoretical calculation - Kaizhen Wu; Rui Li; Xuchao Sun; Fang Shen; Lutao Xue; Shiping Zhang; Xiaoyong Wu; Yubiao Li; Ruan Chi (Journal of Environmental Management, 2025)

Association between sleep quality and serum biomarkers among long-term hot spring bathers: a cross-sectional study - Fen Yang; Yue Zou; Ying-ying Zhang; Hong-xia Li; Yi-hang Xu; Bao-chao Zhang; Lin-xuan Liao; Meng-xi Cao; Rui-xue Wang; Yuan Yuan; Yun Zhou; Da-yong Zeng; et al. (International Journal of Biometeorology, 2025)

Stratigraphy and sedimentology of the upper Pennsylvanian Amushan formation of North China: Palaeogeographic implications for the Eastern Palaeo-Asian Ocean and late palaeozic ice age - Zhongzhao Ding; Shuang Dai; Lingfeng Qin; Chunling Xue; Qiwei Wang; Xin Fan; Xiaojun Ma; Yifeng Hong; Xinnan Fang; Jie Yang; Zhaobin Zhang; Tianqi Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Forest Microclimate as a Driver of Epiphytic Bryophyte Diversity Along a Subtropical Elevational Gradient - Zun Dai; Shi‐chen Xing; S. Robbert Gradstein; Min Li; Shu‐wen Tu; Xing Chen; Xue Yao; Shuang Gao; Rui‐ping Shi; Lu‐yan Tang; Ran Zhang; Zhao‐chen Zhang; et al. (Journal of Biogeography, 2025)
Aim Considering the importance of microclimate in maintaining the diversity of epiphytic bryophytes, we investigated epiphytic bryophytes along an elevational gradient in the subtropical forest of eastern China to unravel the diversity patterns of epiphytic liverworts and mosses along the elevational gradients and the roles of forest microclimates, topographic variables and host plant composition attributes in shaping these elevational diversity patterns. Location Tianmushan National Nature Reserve, Zhejiang, China. Taxon Epiphytic bryophytes. Methods Species diversity patterns of liverworts and mosses were compared based on an inventory of 16 plots along an elevational gradient from 367 to 1470 m. In situ microclimatic data of air temperature and moisture were collected under constant monitoring for over 3 years. Spatial linear models and structural equation models were used to assess the relative roles of the environmental variables in shaping the patterns of species diversity along elevation. Results We found that epiphytic liverwort and moss richness showed different elevational patterns; overall richness patterns of epiphytic bryophytes were largely driven by mosses. Epiphytic mosses exhibited a decline, followed by a hump‐shaped pattern of species richness with increasing elevation, while epiphytic liverworts showed a mid‐elevation plateau with a richness maximum between 800 and 1300 m. Forest microclimate, topography and host plant composition attributes influence epiphytic moss and liverwort patterns differently and interact in a complex way. Overall, species richness of epiphytic liverworts was most strongly affected by microclimate (mean annual air temperature of growing season) and of epiphytic mosses richness by topography (slope). Further, epiphytic liverwort species richness was more influenced by temperature than moisture. Main Conclusions This study highlights the importance of collecting climatic factors at a fine scale (microhabitats) for understanding the patterns and drivers of bryophyte diversity. Further, our findings demonstrate the differences between liverworts and mosses in terms of their response to different environments in the forest ecosystem.

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Application of metallic minerals in wastewater treatment: A review - Xuchao Sun; Yinghao Tang; Rui Li; Kaizhen Wu; Fang Shen; Shiping Zhang; Lutao Xue; Yu Jiang; Xiaoyong Wu (Journal of Water Process Engineering, 2024)

Hexavalent chromium reduces testosterone levels by impairing lipophagy and disrupting lipid metabolism homeostasis: Based on a metabolomic analysis - Qian Xue; Le Zhang; Rui Wang; Jiayunzhu Xu; Chaofan Wang; Shidi Gao; Xin Fang; Chunyang Meng; Rifeng Lu; Li Guo (Toxicology, 2024)

Robust control algorithm designed for robotic legs of lunar-based equipment: Modeling and experiment - Zheng-Han Chen; Zhao-Dong Xu; Rui-Heng Wang; Hong-Fang Lu; Deng-Yun Yu; Jian-Zhong Yang; Xue-Liang Zhao; Zhong-Wei Hu; Sheng-Chao Zhen (Advances in Space Research, 2024)

Correction to: Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

Screening for ferroptosis genes related to endometrial carcinoma and predicting of targeted drugs based on bioinformatics - Rui Wang; Wei Lang; Qian Xue; Le Zhang; Yunzhu Xujia; Chaofan Wang; Xin Fang; Shidi Gao; Li Guo (Archives of Toxicology, 2024)

The mitigation of citric acid on cadmium toxicity in Iris tectorum and its effects on the composition of cell walls - Xiao-Fang Yu; Zhi-Wen Wang; Feng-Lian Chen; Mao-Lin Chen; Xin-Yu Zhang; Jun-Rui Zhang; Wen-Yu Ji; Xue Xiao; Li-Juan Yang; Ting Lei; Xi Li; Ming-Yan Jiang (International Biodeterioration & Biodegradation, 2024)

Wogonin preconditioning of MSCs improved their therapeutic efficiency for colitis through promoting glycolysis - Mengye Wu; Cuiping Li; Xue Zhou; Zhiyong Wu; Jianqi Feng; Xiaolu Guo; Rui Fang; Qinghai Lian; Ming Pan; Xiaorong Lai; Yanwen Peng (Inflammopharmacology, 2024)

Slide-controlling modes and classification system of the mélange high slopes: insight into a disaster-causing mechanism of the Jinsha River mélange belt in the eastern Tibetan Plateau - Hongfu Zhou; Meng Wang; Jingyi Xue; Rui Li; Jinpeng Hu; Jiang Xing; Tian Fang (Bulletin of Engineering Geology and the Environment, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Anthropogenic effects on soils in the eastern Tibetan Plateau revealed by geochemical elemental characteristics - Yuanlong Luo; Shengli Yang; Chen Wen; Xuechao Xu; Xue Xiao; Jiantao Zhou; Xiuyun Yang; Rui Li; Jingzhao Zhang; Xiaomin Fang (Environmental Research, 2024)

Genomic and transcriptomic analysis reveals the genetic diversity and adaptive signatures of Maduo sheep - Li-Na Chang; Xue Gao; Shi-Xin Wu; Rui-Dong Wan; Zhan-Xing Yang; Hai-Mei Zhao; Ke Zhang; Xin-Quan Zhao; You-Gui Fang; Gong-Xue Jia (Small Ruminant Research, 2024)

Two new sesterterpenoids from Atractylodes japonica Koidz. ex Kitam - Yuan-Yuan Zhou; Zhao Sun; Yan Liu; Zhen-Xing Fang; Hui-Rui Gao; Ning-Yu Liu; Xiao-Juan Zhang; Bing-You Yang; Hai-Xue Kuang (Journal of Natural Medicines, 2024)

Framework of land use planning for an energy producing city of Northwest China based on water-energy-food nexus - Zhou Fang; Shi Xue; Changgao Cheng; Qin Zhou; Maroof Ali; Rui Xu; Jinxue Xu; Tonghui Ding; Jie Wang; Zhongde Huang; Xiping Sun; Yang Bai (Journal of Cleaner Production, 2024)

Weak correlations among leaf thermal metrics, economic traits and damages under natural heatwaves - Qiu-Rui Ning; Qiang Li; Hao-Ping Zhang; Yi Jin; Xue-Wei Gong; Rui-Fang Jiao; Emily Patience Bakpa; Han Zhao; Hui Liu (Science of The Total Environment, 2024)

Identification of large yellow croakers (Larimichthys crocea) scavenger receptor genes: Involvement in immune response to Pseudomonas plecoglossicida infection and hypoxia-exposure experiments - Xuanyang Sun; Ning Bao; Chen Rui; Yadong Xue; Qian Fang; Tianyu Zheng; Ziyang Lin; Xiumei Liu; Xubo Wang (Fish & Shellfish Immunology, 2024)

Flat-leaf submerged plants are more sensitive to invasion intensity and water nutrition levels than needle-leaf ones - Yi-Luan Shen; Shu-Yu Zhang; Xiao-Fei Yuan; Kai Sun; Jing-Fang Cai; Jing-Jing Xue; Yu Zhang; Si-Ha A; Li-Juan Yang; Rui Cheng; Hong-Li Li; Guang-Chun Lei (Hydrobiologia, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

Maternal 25(OH)D attenuates the relationship between ambient air pollution during pregnancy and fetal hyperinsulinism - Peng Wang; Wan-jun Yin; Ying Zhang; Xiao-min Jiang; Xiao-guang Yin; Yu-bo Ma; Fang-biao Tao; Rui-xue Tao; Peng Zhu (Chemosphere, 2023)

Enhanced nitrate reduction by metal deposited g-C3N4/rGO/TiO2 Z-schematic photocatalysts: Performance and mechanism comparison of Pd-Cu and Ag - Houfen Li; Shuai Xue; Fang Cao; Cong Gao; Qian Wei; Rui Li; Aijuan Zhou; Sufang Wang; Xiuping Yue (Chemosphere, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

Tailoring enzymatic loading capacity on CdS nanorods@ZnIn2S4 nanosheets 1D/2D heterojunctions: Toward ultrasensitive photoelectrochemical bioassay of tobramycin - Rui Hu; Ben-Fang Xu; Yadong Xue; Zhi-Zhi Xu; Ai-Jun Wang; Li-Ping Mei; Pei Song; Jiu-Ju Feng (Chemosphere, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

Interfacial modulation of organic-inorganic two-dimensional superlattices for efficient electromagnetic wave absorption - Wenjian Wang; Ke Ran; Xingwang Hou; Yilin Huang; Zidong Zhang; Dongxu He; Yuan Fang; Shuai Wang; Yu Liu; Rui Zhao; Xiao-Yu Yang; Weidong Xue (Chemical Engineering Journal, 2023)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Activation of the TREK-1 Potassium Channel Improved Cognitive Deficits in a Mouse Model of Alzheimer’s Disease by Modulating Glutamate Metabolism - Fang Li; Shu-ning Zhou; Xin Zeng; Zhen Li; Rui Yang; Xue-xi Wang; Bin Meng; Wei-lin Pei; Li Lu (Molecular Neurobiology, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Effects of different energy diets on DNA methylation and mRNA expression in follicle stimulating hormone receptor gene promoter region of Duolang sheep during estrus - Bo Liu; Hongjian Li; Weikun Tao; Fei Huang; Xue Rui; Jie Wang; Peng Niu; Di Fang; Qinghua Gao (Molecular Biology Reports, 2022)

Oxygen Metabolism-induced Stress Response Underlies Heart–brain Interaction Governing Human Consciousness-breaking and Attention - Xiao-Juan Xue; Rui Su; Ze-Feng Li; Xiao-Ou Bu; Peng Dang; Si-Fang Yu; Zhi-Xin Wang; Dong-Mei Chen; Tong-Ao Zeng; Ming Liu; Hai-Lin Ma; De-Long Zhang (Neuroscience Bulletin, 2022)

Foetidibacter luteolus gen. nov., sp. nov., isolated from the rhizosphere of Salvia miltiorrhiza - Qian Pu; Guo-hong Zeng; Gui-wei Wang; Ling-er Lu; Ang Li; Xu-rui Cheng; Xue-ying Wang; Ou Li; Cong Sun; Xiu-fang Hu (Archives of Microbiology, 2021)

A novel Schiff base cobalt(III) complex induces a synergistic effect on cervical cancer cells by arresting early apoptosis stage - Wen-Hui Liao; Xue-Qing Song; Yan-Jie Kong; Rui-Dan Bao; Fang-Fang Li; Jie Zhou; Qi-Hua Zhao; Jing-Yuan Xu; Ni Xie; Ming-Jin Xie (BioMetals, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Analysis of Sedimentary Components in Post-haze Concentrated Sugarcane Juice - Rui-Jing Qu; Kai Li; Fang-Xue Hang; Wen Li; Cai-Feng Xie (Sugar Tech, 2018)

Two new compounds from the roots of Ilex pubescens and their cytotoxic activity - Huan Xiong; Fang Zhao; Jiayi Bi; Yang Zhang; Guiyun Zhao; Xue Chen; Yuncong Li; Rui Yan; Qiang Zhao; Hua Qiao; Guogang Zhang (Journal of Natural Medicines, 2016)

Gene expression profiling of Sinapis alba leaves under drought stress and rewatering growth conditions with Illumina deep sequencing - Cai-Hua Dong; Chen Li; Xiao-Hong Yan; Shun-Mou Huang; Jin-Yong Huang; Li-Jun Wang; Rui-Xing Guo; Guang-Yuan Lu; Xue-Kun Zhang; Xiao-Ping Fang; Wen-Hui Wei (Molecular Biology Reports, 2012)

A three-dimensional finite element model of the cervical spine: an investigation of whiplash injury - Jian-Guo Zhang; Fang Wang; Rui Zhou; Qiang Xue (Medical & Biological Engineering & Computing, 2011)

Angiotensin II upregulates Toll-like receptor 4 and enhances lipopolysaccharide-induced CD40 expression in rat peritoneal mesothelial cells - Jun Wu; Xiao Yang; Yun-Fang Zhang; Shu-Feng Zhou; Rui Zhang; Xiu-Qing Dong; Jin-Jin Fan; Mei Liu; Xue-Qing Yu (Inflammation Research, 2009)